2020
DOI: 10.3389/fbioe.2020.00768
|View full text |Cite
|
Sign up to set email alerts
|

Stannic Oxide Nanoparticle Regulates Proliferation, Invasion, Apoptosis, and Oxidative Stress of Oral Cancer Cells

Abstract: Objective: To explore the effects of SnO 2 nanoparticles (NPs) on proliferation, invasion, apoptosis, and oxidative stress of oral cancer. Methods: SnO 2 NPs were prepared and characterized. Oral cancer cell lines CAL-27 and SCC-9 were cultured in vitro. We detected the effects of various concentrations of SnO 2 NPs (0, 5, 25, 50, 100, 200 µg/mL) on the proliferation of oral cancer cells, and observed the morphological changes, and measured the cells ability of migration, invasion and apoptosis condition, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…This suggested that oxidative stress is an essential mediator of cytotoxicity induced by SnO 2 NPs and FA-SnO 2 in SKOV3 cells. Similar observation of the overproduction of ROS on time dependent manner in oral cancer cells after treatment with SnO 2 NPs was previously reported [23]. However, other previous study was reported that the effect of SnO 2 NPs against human breast cancer cells was through intracellular ROS increment in dose dependent manner [25].…”
Section: Discussionsupporting
confidence: 87%
“…This suggested that oxidative stress is an essential mediator of cytotoxicity induced by SnO 2 NPs and FA-SnO 2 in SKOV3 cells. Similar observation of the overproduction of ROS on time dependent manner in oral cancer cells after treatment with SnO 2 NPs was previously reported [23]. However, other previous study was reported that the effect of SnO 2 NPs against human breast cancer cells was through intracellular ROS increment in dose dependent manner [25].…”
Section: Discussionsupporting
confidence: 87%
“…[14,30,37] We observed that this NM produces inflammation and induces pulmonary, hepatic and systemic APR in mice, as shown by the increased levels of neutrophils and plasma SAA3, almost as high as our benchmark materials (TiO 2 and Printex 90). In vitro studies with SnO 2 NM have shown that this material decreases cell viability, affects cell membrane structure and increases reactive oxygen species (ROS) production in different cancer cell lines, including a human lung adenorcarcinoma cell line (A549) [69][70][71]. A recent study compared the effects of SnO 2 and TiO 2 NM on A549 cell and murine monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, zinc-oxide nanoparticles also showed increased cytotoxicity toward CAL-27 oral cancer cells by PINK1/ Parkin-mediated mitophagy [ 18 ]. Similarly, Li et al found that stannic oxide nanoparticles can exert selective cytotoxic effects on oral cancer cells by inhibiting cell proliferation, migration, and invasion abilities and can also induce oxidative stress and apoptosis [ 37 ]. Although the underlying mechanisms are not fully understood, compatible with previous studies, our results suggest that GNSbs induced selective toxicity toward CAL-27 oral cancer cells.…”
Section: Discussionmentioning
confidence: 99%